Exploring Passive Structures in Political and Religious Text: A Corpus-Based Study in Pakistani Writing - Khizar Abbas; Adnan Tahir; Ayyaz Qadeer (Corporum)
Political and religious texts have been widely acknowledged to be distinct registers. The major objective of this study is to investigate the co-occurrence of two types of passive: the Agentless passives(PASS) and the By-passives (BYPA)proposed by Biber (1988) in Pakistani writing concerning variation among the political and religious disciplines. This research has explored and compared the frequencies and patterns of usage of passive structure with promotional varieties studied by Biber (1988) through a multidimensional analysis. The corpus of the research includes 60 texts chosen from Pakistani Register of Policy Documents and Religious Essays. Online sources have been used to retrieve the distribution of 30 texts from each discipline. The frequencies of the passive constructions are counted through AntConc 4.2.4 software after tagging the data in Multidimensional Analysis Tagger (MAT) 2.4. The findings indicated that the structure of agentless passive has occurred significantly more frequently than by-passives in political registers. Moreover, this study confirmed that native English writers have a more lexical variation of agentless passives than by-passives structure in non-native writing. Though limited, the study contributes to clarifying the function of agentless and by-passives across the two registers. This work may be significant for non-native writers and researchers working on disciplinary writing.